Analysis of the Effect of Variation Order on Wastewater Projects - Muhammad Riska Dirgantoro; Sarwono Hardjomuljad (Syntax Idea)
The objectives of this study are: (1) Knowing the factors causing variation order in the Wastewater project. (2) Knowing the effects of variation orders on contractors/service providers in wastewater projects. The type of research used in this study is the quantitative research method. The quantitative research method uses research data in the form of numbers and analyzed using statistics from the results of data collection that have been verified and validated by experts, research variables that will be used in the next questionnaire stage obtained 11 variables of factors causing variation orders and 10 variables of the influence of variation orders on contractors, can be seen in appendix 2. then the following conclusions can be drawn: a) The dominant factors causing the Variation Order in wastewater projects in the DKI Jakarta Government, b) The dominant influence of the Variation Order on service providers/contractors